Continuity and change in China's rural development : collective and reform eras in perspective - Putterman, Louis G. (OUP E-Books., 1993)
A detailed study of rural reform in China, which comprehensively covers Chinese rural development before and after the Mao and Deng reform eras, focusing on the township of Dahe.